Green activation using reducing agents of carbon-based 3D printed electrodes: Turning good electrodes to great. (30th April 2021) - Redondo, Edurne; Muñoz, Jose; Pumera, Martin
Abstract: 3D printing of carbon-based nanocomposites, which combine the electrical properties of carbon additives with the benefits of thermoplastics, has emerged as a promising route towards rapid and low-cost manufacturing of customised-shaped electronic devices with minimised waste. However, their poor electrical activity in their pristine state makes activation post-treatments mandatory to reduce the amount of insulating polymer. These post-treatments typically involve the use of toxic organic solvents or costly thermal annealing methods. Herein, a simple eco-friendly wet-chemical post-treatment is presented for the quick and general activation of carbon-based 3D printed electronic devices by employing reducing agents like ascorbic acid or sodium borohydride. We tested a range of reducing agents, such as sodium borohydride, lithium aluminium hydride, hydrazine and ascorbic acid, as well as a model oxidising agent like hydrogen peroxide. We found that ascorbic acid and sodium borohydride are the most effective chemicals to achieve electrically active devices while preserving the shape and structure of the 3D printed carbon objects. Thus, this work allows the development of advanced carbon-based 3D printed electrodes by employing an eco-friendly activation approach. Graphical abstract: Image 1 Highlights: Reducing agents as alternative green chemicals for the activation of 3DnCEs. Sustainable development by replacing organic solvents for aqueous solutions. General wet-chemical activation for 3DnCEs. Efficient approach to preserve the mechanical properties of the 3D printed objects. Suitability of 3DnCEs for electrochemical achievements.